Purpura with regular shape in an adolescent: Beware of dermatitis artefacta - Chen, Yuhao; Li, Lin; Lu, Jing (Frontiers in Pediatrics, 2022)
Background Purpura is common in pediatric patients, mostly diagnosed as IgA-related vasculitis (Henoch–Schönlein purpura), idiopathic thrombocytopenic purpura (ITP), and thrombotic thrombocytopenic purpura (TTP). However, in some cases, for example, cases with dermatitis artefacta, it could puzzle a physician or pediatrician for a long time, with great challenges in diagnosis. Case presentation We present the case of a 13-year-old boy with recurrent painful purpura on both upper limbs. The physical exam was unremarkable, except for right blepharoptosis and scars from burns. The diagnostic tests were normal. Through repeated communication, the patient was finally diagnosed as having dermatitis artefacta, accompanied by underlying psychological problems. Conclusions Before dermatitis artefacta was diagnosed, we spent a lot of money and effort on the diagnosis. Therefore, in order to determine the diagnosis as soon as possible and save on unnecessary medical expenses, we propose a rapid process for the diagnosis of purpura of dermatitis artefacta in children.